Single Case Design for Clinical Psychology research: what in it’s place in evidence based practice and the process based therapy? (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
This article aims to discuss how single case designs can contribute to research in Clinical Psychology, towards an Evidence-Based Practice of results or processes. Since each research method has strengths and limitations, it is essential to assess how each research design is able to contribute to advances in clinical research, as well as to the therapist´ s practice. The published literature on the subject was consulted, articulating points presented by different authors on such designs. It is concluded that single-subject designs have always had a role within evidence-based practices, although this role is smaller than that attributed to randomized clinical trials. It is argued that thanks to their idiographic characteristics, single-subject designs can play a greater role in this scenario, as well as in Process-Based Therapy.
Keywords: single case design; evidence based practice; process based therapy; clinical psychology research